Effect of Corticosteroids on Mortality in Hospitalized COVID‐19 Patients Not Receiving Invasive Mechanical Ventilation. Issue 6 (19th April 2021) - Fusina, Federica; Albani, Filippo; Granato, Enza; Meloni, Angelo; Rozzini, Renzo; Sabatini, Tony; Stellini, Roberto; Terragnoli, Paolo; Rosano, Antonio; Abu Hilal, Mohammed; Natalini, Giuseppe
Abstract : The most beneficial effect of corticosteroid therapy in COVID‐19 patients has been shown in subjects receiving invasive mechanical ventilation (IMV), corresponding to a score of 6 on the World Health Organization (WHO) COVID‐19 Ordinal Scale for Clinical Improvement (OSCI). The aim of this observational, single‐center, prospective study was to assess the association between corticosteroids and hospital mortality in coronavirus disease 2019 (COVID‐19) patients who did not receive IMV (OSCI 3–5). Included were 1, 311 COVID‐19 patients admitted to nonintensive care wards, and they were divided in two cohorts: (i) 480 patients who received corticosteroid therapy and (ii) 831 patients who did not. The median daily dose was of 8 mg of dexamethasone or equivalent, with a mean therapy duration of 5 (3–9) days. The indication to administer or withhold corticosteroids was given by the treating physician. In‐hospital mortality was similar between the two cohorts after adjusting for possible confounders (adjusted odds ratio (ORadj) 1.04, 95% confidence interval (CI), 0.81–1.34, P  = 0.74). There was also no difference in Intensive Care Unit (ICU) admission (ORadj 0.81, 95% CI, 0.56–1.17, P  = 0.26). COVID‐19 patients with noninvasive mechanical ventilation (NIMV) had a lower risk for ICU admission if they received steroid therapy (ORadj 0.58, 95% CI, 0.35–0.94, P  = 0.03). In conclusion, corticosteroids were overall not associated with a difference in hospital mortality for patients with COVID‐19 with OSCI 3–5. In the subgroup of patients with NIMV (OSCI 5), corticosteroids reduced ICU admission, whereas the effect on mortality requires further studies.